Public Bus Transportation and Student Satisfaction: Evidence from Management Students in Kathmandu Valley - Mishra, Sunira; Basyal, Devid Kumar; Adhikari, Kabita (International Research Journal of MMC, 2026)
Background: In the contemporary period, rapid population growth and urbanization in Kathmandu Valley have intensified demand for public transport. This demand is particularly evident among the college students who use public transportation for daily mobility. The daily use of public services also invites various challenges that students have to go through daily. Purpose: The purpose of the study is to examine management students’ satisfaction towards public bus transport service in Kathmandu Valley. In addition, this study aims to identify challenges faced by management students and propose managerial solutions to improve public bus services in Kathmandu Valley. Design/methodology/approach: This study is based on the service quality (SERVQUAL) model, which argues that public bus service quality qualities like affordability, availability, reliability, comfort, and safety impact the satisfaction of students. In order to find reality, the exploratory research design was chosen as the primary study paradigm. Both descriptive and inferential statistics were used to quantitatively assess the data. The relationships from the sample of 404 respondents were examined using Smart PLS 4.0. Findings: The findings reveal that the majority of the students were female, which implies that female students are more active in using public buses than males. Additionally, it found that every student in the Kathmandu Valley who was surveyed uses public transport, with the majority of them stating that they do so because bus fares are less expensive than those of shared vehicles. This study also demonstrated that affordability, reliability, comfort, and safety have a positive as well as significant impact on student satisfaction using public buses. Further, satisfaction also have significant impact on the actual use of public transport among students. In contrast, availability was found to have an insignificant impact on satisfaction. Conclusion: The study concludes that it is necessary to enhance the service quality of the public transport to enhance utilization among the management students in Kathmandu Valley. Service quality can be increased by focusing on affordable tickets, a reliable transport system, comfortable seats, and the safety of students, especially girls. Besides, a proper schedule should be followed so that students can easily plan their journey based on the timetable.